Formação continuada de professores do ensino médio para a educação especial na perspectiva da educação inclusiva - Noronha, Lílian Freire (2017)
The public policies that emerged in the last two decades related to Special Education are policies whose purpose guaranteed a diversity of rights that allowed, among others, the access of students of this segment to the common classes of Regular Education and that, therefore, contributed to a significant increase of the number of enrollments. In this way, it is necessary to have a training so that the teacher is able to interact in the classroom. Thus, this research had the objective of analyzing the continuing education of teachers who work in the High School of IFAM for the teaching process of Special Education students in the perspective of Inclusive Education. Among the authors used, we highlight Sassaki (2009), Mantoan (2010), Fernandes (2011), Carneiro (2015) and Carvalho (2017). The study presents a qualitative approach to the phenomena, developed from a research Survey as a methodological strategy, with units of analysis focused on the sectors that offer continuing education and on teachers who work in High School. It also uses documentary and bibliographic research as a source of information. Data were collected through questionnaires for the two established units of analysis. Data were collected through questionnaires for the two established units of analysis. The results, for the DIPESP and DIREN sectors, showed that there is a greater approximation with the teachers. On the face of it, these activities performed tend to obtain greater results, since they are elaborated "by" and "for" teachers who know and understand the needs of this segment. However, in these two sectors there are no projects and activities related to Special Education in the form of continuing education. As for NAPNE, it is a nucleus that develops various activities and projects related to Special Education. However, there is little participation of students and teachers of the Institution. As for teachers, the most expressive result was 92.0% of respondents who did not perform any continuing education related to Special Education in the last three years. Positively, 53.1% of the research participants have read or heard about the National Policy on Special Education in the perspective of Inclusive Education against the percentage of 34.7% who did not hear about it. Related to NAPNE, 72.0% know this nucleus, but only 4.0% have already taken some courses in it. However, in a positive way, 81.6% of these respondents would be willing to take a course in NAPNE with this approach. The conclusion is that there is a need for a reformulation of the continuing education structure, related to Special Education, for IFAM teachers. Regarding the contributions, the research contributed to the clarification about how the ongoing formation of teachers who work with Special Education students is occurring. As well as to put in discussion this theme in the academic environment to try to provide reflections that come to materialize concrete actions for the quality of the students' teaching.